The role of the nurse in the perioperative care of hernia patients - Szczęsny, Wojciech; Siewkowska, Monika; Dąbrowiecki, Stanisław; Reśliński, Adrian (Nursing Problems / Problemy Pielęgniarstwa, 2012)
The manuscript presents basic concepts from the epidemiology and pathogenesis of hernias. The authors discuss the role of the nurse in perioperative care of patients with abdominal hernias, with a special focus on the diagnosis and treatment of early and late complications. Appropriate preoperative preparation and perioperative care are key factors influencing treatment outcomes. The ever-increasing ubiquity of synthetic materials calls for a careful observation of the rules of aseptic and antiseptic surgery at every stage of the treatment process. This is a particular problem in individuals with large abdominal hernias, who often have significant comorbidities such as diabetes or cardiopulmonary insufficiency. As general longevity increases, one must expect an increase in the numbers of patients suffering from various types of hernias, who will have special nursing requirements. Nursing Topics 2012; 20 (4): 539–545